2018
DOI: 10.1108/ijoes-11-2017-0211
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of financial inclusive policy in Indian economy

Abstract: Purpose -This study attempts to critically assess one of the financial inclusion policy "Pradhan Mantri Jan Dhan Yojna" introduced by the government of India in 2014.Design/methodology/approach -Number of bank accounts opened (rural, urban and overall) under the policy, total balance in such account and total number of debit cards issued till October, 2017 were taken as the criterion variables. The macroeconomic indicators, infrastructure, literacy, regional dummy and percentage labour participation were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The study also finds that for female-headed households, education and wage are important factors explaining the access to finance, whereas, political and social factors are more relevant for explaining the use of finance. Sharma et al (2018) analyzes the factors, which promote the PMJDY scheme. The results show that infrastructure such as road is the most significant factor explaining the outreach of the PMJDY scheme.…”
Section: Introductionmentioning
confidence: 99%
“…The study also finds that for female-headed households, education and wage are important factors explaining the access to finance, whereas, political and social factors are more relevant for explaining the use of finance. Sharma et al (2018) analyzes the factors, which promote the PMJDY scheme. The results show that infrastructure such as road is the most significant factor explaining the outreach of the PMJDY scheme.…”
Section: Introductionmentioning
confidence: 99%
“…12. A Look at the Indian Economy's Financial Inclusive Policy; Sharma, Bhattacharya, and Thukral (2018) and the success of the PMJDY. They found that socio-economic, environmental, and educational factors play a key part (Sharma et al, 2018).…”
Section: Examining the Effects Of Drivers Of Financial Inclusion Sust...mentioning
confidence: 99%
“…A significant body of work is available to present the determinants of financial inclusion in India. For instance, branch networks (Kumar 2013), self-help groups and education (Bhanot et al 2012); socioeconomic factors (Clámara et al 2014;Rastogi and Ragabiruntha 2018); domestic agriculture to gross domestic product (GDP), literacy ratio, population density, and urbanization (Yadav and Sharma 2016); economic growth (Sharma 2016); bank branch quantity, and credit deposit ratio on GDP (Iqbal and Sami 2017); infrastructure (Sharma et al 2018); poverty and inequality (Erlando et al 2020); and social safety (Didenko et al 2020). People are being helped to escape poverty and are being connected to economic opportunities through formal financial services, including those that may be accessed over the phone.…”
Section: Introductionmentioning
confidence: 99%